2015
DOI: 10.1016/j.antiviral.2015.01.015
|View full text |Cite
|
Sign up to set email alerts
|

A monoclonal antibody binds to threonine 49 in the non-structural 1 protein of influenza A virus and interferes with its ability to modulate viral replication

Abstract: The emergence of resistant influenza A viruses highlights the continuous requirement of new antiviral drugs that can treat the viral infection. Non-structural 1 (NS1) protein, an indispensable component for efficient virus replication, can be used as a potential target for generating new antiviral agents. Here, we study the interaction of 2H6 monoclonal antibody with NS1 protein and also determine whether influenza virus replication can be inhibited by blocking NS1. The 2H6-antigen binding fragment (Fab) forms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 33 publications
2
11
0
Order By: Relevance
“…These predictions are in agreement with the results shown in Fig. 2 and in our previous publication 29 . However, this model also predicted that R44 of NS1(RBD) could be involved in the interaction with 2H6-Fab because it was in close proximity to two residues in VL-CDR1.…”
Section: Resultssupporting
confidence: 94%
See 3 more Smart Citations
“…These predictions are in agreement with the results shown in Fig. 2 and in our previous publication 29 . However, this model also predicted that R44 of NS1(RBD) could be involved in the interaction with 2H6-Fab because it was in close proximity to two residues in VL-CDR1.…”
Section: Resultssupporting
confidence: 94%
“…This was conducted by using HADDOCK on 192 water-refined models, including an analysis of energy contributions from Van der Waals interaction, electrostatic interaction, restraints violation and buried surface area 32 . As comparative ELISA in this and previous studies 29 showed that residues N48 and T49 in NS1(RBD) are important for the interaction with mAb 2H6, they were defined as active residues involved in the binding interaction to generate a series of models of the NS1(RBD) and 2H6-Fab complex.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Some of the identified phosphorylation sites occur at sites conserved between various IAV strains with a potential functional relevance. For example, we identified an NS1 modification at Thr49, which is immediately adjacent to the previously identified phosphorylation site at Ser48 in a region that is directly involved in RNA binding and therefore functionally relevant (47,49,50). In order to obtain insight into the structural consequences of Ser48/Thr49 phosphorylation, published NS1 structures (51, 52) were used as the templates to model the structure of SC35M NS1 using the Swiss-Model server (Fig.…”
Section: Resultsmentioning
confidence: 99%